2019
DOI: 10.3389/fnins.2019.00868
|View full text |Cite
|
Sign up to set email alerts
|

The Relevance of Insulin Action in the Dopaminergic System

Abstract: The advances in medicine, together with lifestyle modifications, led to a rising life expectancy. Unfortunately, however, aging is accompanied by an alarming boost of age-associated chronic pathologies, including neurodegenerative and metabolic diseases. Interestingly, a non-negligible interplay between alterations of glucose homeostasis and brain dysfunction has clearly emerged. In particular, epidemiological studies have pointed out a possible association between Type 2 Diabetes (T2D) and Parkinson’s Disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 223 publications
(239 reference statements)
3
75
0
2
Order By: Relevance
“…This suggests that db/db mice activate compensatory mechanisms to deliver DAT to the plasmalemmal membrane, possibly related to differences between both mouse models in insulin levels known to impact dopaminergic neurotransmission. [81][82][83][84] Consistent with our data, decreased DAT binding sites have been observed in diabetic patients with or without PD. 15 Decreased VMAT2 levels may reflect decreased number or size of synaptic vesicles, in consonance with parallel low levels of Syb2, and suggest that the sequestration of axonal dopamine into vesicles is compromised in diabetic mice, favoring its accumulation in the cytosol, as indicated previously.…”
Section: I a B E T E Ssupporting
confidence: 91%
“…This suggests that db/db mice activate compensatory mechanisms to deliver DAT to the plasmalemmal membrane, possibly related to differences between both mouse models in insulin levels known to impact dopaminergic neurotransmission. [81][82][83][84] Consistent with our data, decreased DAT binding sites have been observed in diabetic patients with or without PD. 15 Decreased VMAT2 levels may reflect decreased number or size of synaptic vesicles, in consonance with parallel low levels of Syb2, and suggest that the sequestration of axonal dopamine into vesicles is compromised in diabetic mice, favoring its accumulation in the cytosol, as indicated previously.…”
Section: I a B E T E Ssupporting
confidence: 91%
“…Clinical manifestations of both diseases are caused by the destruction of specific cells, which are the pigmented dopaminergic cells in PD, and the beta-pancreatic cells in DM. The loss of these cells results in decreased insulin in DM and dopamine in PD [6].…”
Section: Introductionmentioning
confidence: 99%
“…Insulin resistance also correlates with the progression of PD [ 35 ]. Finally, a recent study concluded that DM can possibly increase the risk of development of Parkinson-like pathology and aggravate the disease phenotype [ 102 ].…”
Section: C-reactive Proteinmentioning
confidence: 99%
“…Some studies showed that EGF may be linked to the development of microvascular complications in diabetes [ 51 ]. For example, patients with type 1 DM and microangiopathy have higher serum EGF concentrations compared to those without [ 102 ]. VEGF, in turn, is mainly responsible for stimulating endothelial cell proliferation and migration, collagen production and macrophage chemotaxis [ 52 ].…”
Section: C-reactive Proteinmentioning
confidence: 99%